2009
DOI: 10.1038/hr.2009.152
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled hypertension based on morning and evening home blood pressure measurements from the J-HOME study

Abstract: Imai, the J-HOME Study Group 7We evaluated the control condition of morning and evening home blood pressure (BP) and compared patients who had isolated uncontrolled morning hypertension and those who had sustained uncontrolled (morning and evening) hypertension using data from the Japan Home versus Office Blood Pressure Measurement Evaluation study. We evaluated 3303 treated hypertensive patients (mean age, 66.2 ± 10.5 years; men, 44.7%) in Japan. We classified patients into controlled hypertension, isolated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…2, 3 Strict BP control over 24 h, including the night-time and early morning hours, is crucial, as the average BP level over 24 h, nocturnal and early morning BP are more closely associated with target organ damage and cardiovascular events than office BP. 4, 5, 6 In clinical practice, however, it is not infrequent that existing antihypertensive drugs fail to provide an adequate antihypertensive effect that is sustained over 24 h. 7 In the J-MORE (Jichi Morning Hypertension Research) study, 60.7% of treated hypertensives with well-controlled clinic BP were found to have masked morning hypertension (systolic BP (SBP) ⩾135 mm Hg; diastolic BP (DBP) ⩾85 mm Hg), and only 16.4% of patients overall had well-controlled clinic and morning BP levels. 8 These findings may be related to the limited BP-lowering effect and duration of action of some antihypertensives, highlighting the importance of treatments that control BP over a full 24-h period when administered once daily.…”
Section: Introductionmentioning
confidence: 99%
“…2, 3 Strict BP control over 24 h, including the night-time and early morning hours, is crucial, as the average BP level over 24 h, nocturnal and early morning BP are more closely associated with target organ damage and cardiovascular events than office BP. 4, 5, 6 In clinical practice, however, it is not infrequent that existing antihypertensive drugs fail to provide an adequate antihypertensive effect that is sustained over 24 h. 7 In the J-MORE (Jichi Morning Hypertension Research) study, 60.7% of treated hypertensives with well-controlled clinic BP were found to have masked morning hypertension (systolic BP (SBP) ⩾135 mm Hg; diastolic BP (DBP) ⩾85 mm Hg), and only 16.4% of patients overall had well-controlled clinic and morning BP levels. 8 These findings may be related to the limited BP-lowering effect and duration of action of some antihypertensives, highlighting the importance of treatments that control BP over a full 24-h period when administered once daily.…”
Section: Introductionmentioning
confidence: 99%
“…114,120 In the Ohasama study, in which evening BP was measured under the abovementioned conditions, BP in the morning was a few mm Hg higher than that in the evening. 121 This was especially true in the hypertensive population of Ohasama, for whom the difference in SBP was 10-20 mm Hg. 119 Such differences were also confirmed in Western countries, while several reports confirmed a higher home BP in the evening than that in the morning.…”
Section: ) Measurement Procedures In the Eveningmentioning
confidence: 97%
“…114,119 The major causes of this difference in BP between the morning and evening are reported to be antihypertensive treatment, alcohol intake and taking a bath. [120][121][122] Those who exhibit large morning-evening differences in BP have marked target organ damage, such as left ventricular hypertrophy. [123][124][125][126] However, home BP measured in the evening also has a high prognostic significance.…”
Section: Masked Hypertensionmentioning
confidence: 99%
“…4-8 On home BP self-measurement, morning hypertension was observed in >60% of patients receiving anti-hypertensive drugs. 9 It was suggested that the reduction in morning SBP reduced UAE and improved renal function in patients with diabetic and non-diabetic nephropathy. 10,11 Standard treatment for morning hypertension, however, has not been established.…”
Section: Discussionmentioning
confidence: 99%